2018
DOI: 10.21199/wb49.1.1
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Hawaii Bird Records Committee

Abstract: The Hawaii Bird Records Committee (HBRC) was formed in 2014 to provide a formal venue for reviewing bird reports in the Hawaiian Islands and to maintain and periodically update the checklist of birds of the Hawaiian Islands. This is the first report of the HBRC. From 2014 to 2016, the HBRC reviewed 46 reports involving 33 species, including 20 species not recorded previously in the Hawaiian Islands, nine species reported previously that were based only on visual documentation at the time, one re-evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In addition, at least 11 other S. l. brewsteri have been photographed at sea in the region, including (from east to west): 2,000 km southwest of Galápagos on 6 May 2017 (Greenfelder 2017); 1,650 km northeast of the Marquesas on 30 January 2020 (Pennington 2020); 1250 km and 830 km east of Hawaii Island on 9 and 10 January 2016 (Mathre 2016 a , b ); from Makapu'u Point, Oahu, on 13 July 2022 (Apuna 2022); off Barber's Point, Oahu on 8 March 2009 (C. Babbitt unpubl. ); 250 km west of Kauai on 5 April 2018 (VanderWerf 2018 b ); 340 km west of Kure Atoll on 23 September 2017 (Ü 2017); off Saipan in 2018 (Ü unpubl. ); 13–35 km east of Miyako, Iwate, Japan on 18 and 23 July 2020 (Muzika 2020 a ), and 10 km southwest of Mikurajima, Japan on 12 July and 17 October 2020 (Muzika 2020 b , c ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, at least 11 other S. l. brewsteri have been photographed at sea in the region, including (from east to west): 2,000 km southwest of Galápagos on 6 May 2017 (Greenfelder 2017); 1,650 km northeast of the Marquesas on 30 January 2020 (Pennington 2020); 1250 km and 830 km east of Hawaii Island on 9 and 10 January 2016 (Mathre 2016 a , b ); from Makapu'u Point, Oahu, on 13 July 2022 (Apuna 2022); off Barber's Point, Oahu on 8 March 2009 (C. Babbitt unpubl. ); 250 km west of Kauai on 5 April 2018 (VanderWerf 2018 b ); 340 km west of Kure Atoll on 23 September 2017 (Ü 2017); off Saipan in 2018 (Ü unpubl. ); 13–35 km east of Miyako, Iwate, Japan on 18 and 23 July 2020 (Muzika 2020 a ), and 10 km southwest of Mikurajima, Japan on 12 July and 17 October 2020 (Muzika 2020 b , c ).…”
Section: Resultsmentioning
confidence: 99%
“…In September 2022, E. VanderWerf observed five S. l. brewsteri females on Moku Manu, all of which were unpaired. On Laysan, a nest with a male brewsteri and female plotus was reported in 1998 (VanderWerf et al 2008), but reexamination of photos using identification criteria from VanderWerf (2018) revealed that the female was S. l. brewsteri , representing another instance in which a male and female brewsteri paired with each other amid large numbers of male and female plotus . On Tern Island, only males were reported in 2003 and only females were observed in 2018 by E. VanderWerf, and no nests were found in either year.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations